2016
DOI: 10.3390/ijms17121921
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin down Regulates Hepcidin by Inhibiting NF-κB and IL6/JAK2/STAT3 Pathways in BV-2 Microglial Cells Treated with Lipopolysaccharide

Abstract: Aspirin down regulates transferrin receptor 1 (TfR1) and up regulates ferroportin 1 (Fpn1) and ferritin expression in BV-2 microglial cells treated without lipopolysaccharides (LPS), as well as down regulates hepcidin and interleukin 6 (IL-6) in cells treated with LPS. However, the relevant mechanisms are unknown. Here, we investigate the effects of aspirin on expression of hepcidin and iron regulatory protein 1 (IRP1), phosphorylation of Janus kinase 2 (JAK2), signal transducer and activator of transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Experiments with cell cultures have shown that LPS induces IL-6 expression in microglia, which then induces hepcidin production in astrocytes and probably neurons [ 54 , 55 ]. LPS can induce hepcidin production in microglia as well [ 56 , 57 ], while IL-6 was shown to increase hepcidin expression in neurons through phosphorylation of STAT3 [ 55 ]. Studies with cell cultures have revealed that, in astrocytes and neurons, hepcidin induces not only FPN downregulation, but also TFR1 and DMT1 downregulation [ 58 , 59 ].…”
Section: Hepcidin Production and Action In The Brainmentioning
confidence: 99%
“…Experiments with cell cultures have shown that LPS induces IL-6 expression in microglia, which then induces hepcidin production in astrocytes and probably neurons [ 54 , 55 ]. LPS can induce hepcidin production in microglia as well [ 56 , 57 ], while IL-6 was shown to increase hepcidin expression in neurons through phosphorylation of STAT3 [ 55 ]. Studies with cell cultures have revealed that, in astrocytes and neurons, hepcidin induces not only FPN downregulation, but also TFR1 and DMT1 downregulation [ 58 , 59 ].…”
Section: Hepcidin Production and Action In The Brainmentioning
confidence: 99%
“…In animal models with brain inflammation and increased oxidative stress, direct and indirect suppression of local and systemic hepcidin offers neuroprotection ( Chen et al, 2015 ; Li W.-Y. et al, 2016 ; Pan et al, 2016 ; Xiong et al, 2016 ).…”
Section: The Rationale For Using Hepcidin Therapeutics In Neurodegenementioning
confidence: 99%
“…Based on the accumulating evidence about the role of inflammation on cellular iron content, it is reasonable to assume that neuroprotection can be achieved by blocking the inflammatory pathways through already established drugs. One such drug is acetylsalicylic acid, which has already been used in cultured cells to protect neuronal cells and microglia from inflammation-induced damage ( Li W.-Y. et al, 2016 ; Huang et al, 2018 ) ( Table 1 ).…”
Section: The Rationale For Using Hepcidin Therapeutics In Neurodegenementioning
confidence: 99%
“…Substantia nigra is rich in microglia and astroglia, which are the main actors in neuroinflammatory responses, and their double role at the interface between immune and neurophysiological responses was widely studied [30]. Previous studies demonstrated that ASA down-regulated the inflammatory condition in activated microglia induced by lipopolysaccharide (LPS) [31]. In the present study, co-administration of ASA and L-DOPA At present, this study provides the first evidence for the synergistic therapeutic strategy of ASA combined with L-DOPA in PD and LID.…”
Section: Discussionmentioning
confidence: 99%